Prosthetics and Orthotics 2021
DOI: 10.5772/intechopen.96090
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Orthopedic Treatments

Abstract: To determine the effectiveness and satisfaction with orthopodologic treatments in users of the University Clinic of podiatry at the University of A Coruña, according to various parameters. After approval from the ethics committee of the University of A Coruña, an observational retrospective study (n = 125). We analyzed the effectiveness and satisfaction with the orthopodologic treatments depending on the reason for consultation, diagnosis, treatment and goals of treatment. We performed a descriptive analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In this study, there was no significant relationship between the mean body mass index and patient satisfaction (P=0.067, P=0.454, and P= 0.110, respectively). This result is consistent with the studies by Cristina Gonzalez-Martin [12] and inconsistent with the study by Holtkamp FC [11]. Gonzalez's study revealed that patients with a higher body mass index had a lower level of satisfaction, but this effect was not significant (P=0.132).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In this study, there was no significant relationship between the mean body mass index and patient satisfaction (P=0.067, P=0.454, and P= 0.110, respectively). This result is consistent with the studies by Cristina Gonzalez-Martin [12] and inconsistent with the study by Holtkamp FC [11]. Gonzalez's study revealed that patients with a higher body mass index had a lower level of satisfaction, but this effect was not significant (P=0.132).…”
Section: Discussionsupporting
confidence: 60%
“…Also, people with a higher body mass index were more dissatisfied with orthotic services [11]. Gonzalez's study revealed that patients with a higher body mass index had a lower level of satisfaction, but this effect was not significant (P=0.132) [12].…”
Section: Introductionmentioning
confidence: 97%